Association between inflammatory markers and survival in comatose, resuscitated out-of-hospital cardiac arrest patients. (31st December 2022) - Toftgaard Pedersen, Anne; Kjaergaard, Jesper; Hassager, Christian; Frydland, Martin; Hartvig Thomsen, Jakob; Klein, Anika; Schmidt, Henrik; Møller, Jacob Eifer; Wiberg, Sebastian
Abstract: Objectives: Prognostication after out-of-hospital cardiac arrest (OHCA) remains challenging. The inflammatory response after OHCA has been associated with increased mortality. This study investigates the associations and predictive value between inflammatory markers and outcome in resuscitated OHCA patients. Design: The study is based on post hoc analyses of a double-blind controlled trial, where resuscitated OHCA patients were randomized to receive either exenatide or placebo. Blood was analyzed for levels of inflammatory markers the day following admission. Primary endpoint was time to death for up to 180 days. Secondary endpoints included 180-day mortality and poor neurological outcome after 180 days, defined as a cerebral performance category (CPC) of 3 to 5. Results: Among 110 included patients we found significant associations between higher leucocyte quartile and increasing mortality in univariable analysis (OR 2.6 (95%CI 1.6–4.2), p < .001), as well as in multivariable analysis (OR 2.1 (95%CI 1.1–4.0), p = .02). A significant association was found between higher neutrophil quartile and increasing mortality in univariable analysis (OR 3.0 (95%CI 1.8–5.0), p < .001) as well as multivariable analysis (OR 2.4 (95%CI 1.2–4.6), p = .01). Leucocyte and neutrophil levels were predictive of poor outcome after 180 days with area under the receiver operating characteristics curves of 0.79 and 0.81, respectively. We found no associations between CRP and lymphocyte levels versus outcome. Conclusions: Total leucocyte count and neutrophil levels measured the first day following OHCA were significantly associated with 180-day all-cause mortality and may potentially act as early predictors of outcome. Clinical trial registration: www.clinicaltrials.gov, unique identifier: NCT02442791